Chiral supramolecular polymerization leading to eye differentiable circular polarization in luminescence. Issue 64 (13th July 2016) - Kumar, Jatish; Marydasan, Betsy; Nakashima, Takuya; Kawai, Tsuyoshi; Yuasa, Junpei
Abstract : A simple methodology to tune the chiroptical properties of a europium(iii ) complex in helical supramolecular polymerization is demonstrated wherein aggregation leads to enhanced luminescence dissymmetry. Abstract : This work demonstrates a simple methodology to tune the chiroptical properties of chiral europium(iii ) complexes by supramolecular polymerization. Helical aggregation of the cesium derivative has updated the highest luminescence dissymmetry factor to date leading to naked eye visualization of circular polarized luminescence using circularly polarized filters.